KESENJANGAN HARAPAN KETERAMPILAN YANG DIMILIKI OLEH SARJANA AKUNTANSI - Tubagus Ismail (Jurnal Riset Akuntansi Terpadu, 2018)
The purpose of this article is to explore generic skills possessed by accounting graduates at universities in Banten Province. Data was collected through questionnaires, by conducting non-parametric analysis. The findings of this study are the main causes of the gap in expectations of accounting graduates is the low skill and competence of teachers to produce graduates to have a successful career. The second finding is that teachers in universities actually know the skill needs needed by graduates. The third finding is that the graduates indicated by the company they work for do not fulfill the expected skills and competencies. This finding reflects the importance of curriculum renewal, improving the competence of accounting lecturers.